The Effect of Food Delivery and Relationship Marketing Services on Consumer Purchase Decisions on Culinary MSMEs in Tanjung Priok Moderated with Entrepreneurship Self-Efficiency - Kustiadi Basuki; Devy Novianti (Budapest International Research and Critics University, 2022)
This study aims to prove the effect of Food Delivery Services and Relationship Marketing on Purchase Decisions and the moderating impact of Entrepreneurial Self-Efficacy. And provide evidence on impact and provide recommendations to MSMEs to improve purchasing decision strategies. The population in this study are consumers who perform and use Food Delivery Services in Jakarta as many as 205 people, with probability sampling samples using Structural Equation Modeling (SEM) analysis techniques with partial least squares (PLS) through SmartPLS software. Data collected by questionnaires that have been tested for validity and reliability. The results of the first hypothesis testing, it was found that the relationship between Food Delivery Services and Purchase Decisions had a positive or significant effect on Tanjung Priok Culinary MSMEs. The results of the second hypothesis tester, it was found that the relationship between Relationship Marketing and purchasing decisions has a negative or insignificant effect on Tanjung Priok Culinary MSMEs. The results of the third hypothesis tester, it was found that the relationship of Entrepreneurial Self-Efficacy to Purchasing Decisions had a positive or significant effect on Tanjung Priok Culinary MSMEs. The results of the fourth hypothesis tester, it was found that Food Delivery Service on purchasing decisions could not be moderated by Entrepreneurial Self-Efficacy and was not significant in Tanjung Priok Culinary MSMEs. The results of the fifth hypothesis tester, it was found that Relationship Marketing on Purchase Decisions could not be moderated by Entrepreneurial Self-Efficacy and not significant in Tanjung Priok Culinary MSMEs. The importance of Food Delivery Service on purchasing decisions because it directly affects the Tanjung Priok Culinary MSMEs and is also able to moderate the influence of another independent variable, namely Relationship Marketing.